2011
DOI: 10.1097/mpa.0b013e31821f2645
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of High-Fat-Diet Feeding on Rat Pancreas Oxidative Stress

Abstract: These results confirm the existence of a sex dimorphism in pancreas oxidative status in both control and high-fat-diet feeding situations, with female rats showing higher protection against oxidative stress, thus maintaining pancreatic function and contributing to a lower risk of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…This is consistent with the findings in both rodents and humans, demonstrating a gender difference in oxidative stress, with females characterized by lower levels of oxidative stress than males [22]. Reactive oxygen species (ROS) production was lower and activity of antioxidant enzymes was higher in females compared to males [23,24]. Accordingly, NAC administration during pregnancy and lactation increased the resistance of male islets to oxidative stress, while females were not affected, suggesting that NAC is involved in the programming of the antioxidant defense mechanisms, which enables better accommodation with oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the findings in both rodents and humans, demonstrating a gender difference in oxidative stress, with females characterized by lower levels of oxidative stress than males [22]. Reactive oxygen species (ROS) production was lower and activity of antioxidant enzymes was higher in females compared to males [23,24]. Accordingly, NAC administration during pregnancy and lactation increased the resistance of male islets to oxidative stress, while females were not affected, suggesting that NAC is involved in the programming of the antioxidant defense mechanisms, which enables better accommodation with oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…Catalase activity levels were found to be the same between genders in the brain, heart, lung and heart, but higher in the female kidney . However, some studies showed no difference in catalase activity levels between males and females . These data suggest that catalase activity and thus hydrogen peroxide degradation may not be affected by gender and sex hormones.…”
Section: Gender and Oxidative Stressmentioning
confidence: 84%
“…This suggests that there is a gender‐specific difference in the pathophysiology of AITP. In regard to pancreatic disease, female rats exhibit higher protection against oxidative stress and thus have a lower risk of developing insulin resistance compared to male rats . In addition to these disease states, oxidative stress and gender have been shown to be associated with ageing.…”
Section: Gender Oxidative Stress and Diseasesmentioning
confidence: 99%
“…However, some studies did not demonstrate differences in the level of catalase activity between men and women [56,57,62]. Thus, the studies cited above indicate that gender and sex hormones do not affect catalase activity, and thus, the degradation of hydrogen peroxide [63].…”
Section: Discussionmentioning
confidence: 96%